Histopathological Findings of Endometrial Samples and its Correlation Between the Premenopausal and Postmenopausal Women in Abnormal Uterine Bleeding - Sharma, S; Makaju, R; Shrestha, S; Shrestha, A (Kathmandu University Medical Journal, 2015)
Background Abnormal uterine bleeding is considered as one of the most common problems among women. The therapy is incomplete without knowing the underlying pathology.Objectives To determine the types and frequency of endometrial pathologies in patients presenting with abnormal uterine bleeding at Dhulikhel Hospital Kathmandu university Hospital.Methods This is retrospective study total 100 cases were included over a period of one year of Abnormal Uterine bleeding.Results Out of 100 cases of Abnormal uterine bleeding, 61% were due to non-organic cause with a commonest histopathological findings proliferative endometrium. 27% cases were due to organic cause with pregnancy related condition as most common finding. 12% were reported as inadequate. The rate of postmenopausal bleeding declined with increasing age in the postmenopausal period and endometritis was the predominant finding.Conclusion There is an age specific association of Abnormal uterine bleeding with increased incidence in perimenopausal age group. Postmenopausal bleeding declined with increasing with endometritis the most common finding. Dilation and curettage is helpful to exclude other organic pathology. It is useful for diagnosis and to know pathological incidence of organic lesions in cases of Abnormal uterine bleeding prior to surgery.Kathmandu University Medical Journal Vol.12(4) 2014; 275-278